Occupational Therapy Within an Outpatient Cardiac Program: Development and Outcome Study - Lindsey, Jacob (Archives of physical medicine and rehabilitation, 2025)
To assess the feasibility and functional outcomes of a Cardiac Wellness Program in an outpatient setting. The initial program design was based within the Person, Environment, Occupation, and Performance Model with additional design supplementation from the OT Wellness Model and social work Psycho-Education Model. Patients referred from the Outpatient Cardiac Exercise program were assessed using the Canadian Occupational Performance Measure, Cognitive Performance Test: Medication Subtest, and the Activity Card Sort. Patients underwent a 4-week program consisting of 2 individual sessions (evaluation and discharge) and 5 group classes that provided education and training on a variety of subjects surrounding cardiac symptoms, wellness education, medication routine, family relationships, socialization, and occupational engagement. Outpatient - large, general metropolitan area. Fourteen patients (N=14; 50% male, 50% female) participated across 5 cohorts between September 2023 and March 2024. Referrals were made on an ad hoc basis by the cardiac NP. Patients underwent a 4 week program consisting of 2 individual sessions (evaluation and discharge), and 5 group classes (capped at 4 persons each cohort) that provided education and training on a variety of subjects surrounding cardiac symptoms, wellness education, medication routine, family relationships, socialization, and occupational engagement. The therapist-to-patient ratio was capped at 1:4. Sessions and classes varied in duration based on course material and lateness to group appointments but ranged from 30 minutes to 3 hours. Canadian Occupational Performance Measure, Cognitive Performance Test: Medication Subtest, and the Activity Card Sort. OT program material and interventions had to be immediately readjusted in the first cohort due to timing between initial diagnosis/hospitalization to presentation to cardiac OT program (≥6 months). Prior to treatment patients demonstrated deficits in cognition, reduced occupational engagement, and deficits in functional performance. At the completion of the 4-week program, patients reported improved functional performance in self-selected occupations. The program generated referrals to 6 different specialty services. The Outpatient OT Cardiac Wellness program is beneficial and cost-effective, but OT in cardiac outpatient care is underused and under-researched. This wellness focused program offers holistic treatment and comprehensive treatment aimed at improving functional outcomes while simultaneously improving patient and family ability to manage chronic cardiac conditions. I was instrumental in creating this program but have no conflicts of interest or other disclosures.